Chronic active Epstein–Barr virus infection: a bi-faceted disease with inflammatory and neoplastic elements - Ayako Arai (Immunological Medicine, 2019)
Chronic active Epstein–Barr virus infection (CAEBV) is one of the Epstein–Barr virus (EBV)-positive T- or NK-cell lymphoproliferative diseases. It is characterized by clonal proliferation of EBV-infected T or NK cells and their infiltration into systemic organs, leading to their failure. Inflammatory symptoms, fever, lymphadenopathy and liver dysfunction are main clinical findings of CAEBV. EBV itself contributes to the survival of the host cells via induction of CD40 and CD137 expression and constitutive activation of NF-κB. Accumulation of gene mutations in the infected cells may lead to the development of highly malignant lymphoma or leukemia. Furthermore, constitutive activation of STAT3 is detected in the infected cells, which not only promotes cell survival but also enhances production of inflammatory cytokines. Currently, allogeneic hematopoietic stem cell transplantation (allo-HSCT) is the only effective treatment strategy for eradication of EBV-infected T or NK cells. However, active disease at the time of allo-HSCT (defined as presence of fever, liver dysfunction, progressive skin lesions, vasculitis or uveitis) is a negative prognostic factor. Establishment of chemotherapy regimens for effective resolution of disease activity in patients with CAEBV is a key imperative. Based on the recently unraveled molecular mechanisms CAEBV development, pathways mediated by NF-κB or JAK/STAT are potential novel therapeutic targets.